2008
DOI: 10.1007/s00198-008-0764-2
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitamin K and D deficiency and decreased BMD in inflammatory bowel disease

Abstract: IBD patients have high prevalence of decreased BMD and vitamin K and D deficiency probably caused by malabsorption of these vitamins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 46 publications
1
58
0
Order By: Relevance
“…In a more recent analysis in Japanese IBD patients, similar vitamin K deficiency was documented and shown to be more prominent in CD that in UC (59). Undercarboxylated osteocalcin was also elevated in CD patients.…”
Section: Vitamin K Status In Ibd Patientsmentioning
confidence: 71%
See 1 more Smart Citation
“…In a more recent analysis in Japanese IBD patients, similar vitamin K deficiency was documented and shown to be more prominent in CD that in UC (59). Undercarboxylated osteocalcin was also elevated in CD patients.…”
Section: Vitamin K Status In Ibd Patientsmentioning
confidence: 71%
“…Undercarboxylated osteocalcin was also elevated in CD patients. There was no significant difference in vitamin K intake between CD and UC; therefore, malabsorption of vitamin K was postulated to be the likely contributor (59). Although vitamin K absorption in inflammatory conditions has not been studied, one case report with a small bowel CD patient treated with warfarin for deep vein thrombosis showed resistance to oral vitamin K for reversal of overanticoagulation (37).…”
Section: Vitamin K Status In Ibd Patientsmentioning
confidence: 99%
“…Malabsorption rather than dietary insufficiency is the likely main underlying mechanism leading to fat-soluble vitamin deficiencies [Kuwabara et al 2009] which, in turn, can be associated with metabolic bone disorders [Kuwabara et al 2009]. Vitamin D deficiency can, of course, result in osteomalacia.…”
Section: Protein Energy Malnutritionmentioning
confidence: 99%
“…Kuwabara et al observed greater bone mineral density (BMD) deficiencies in the distal radius (cortical bone) compared with the lumbar spine (trabecular bone). This suggests factors other than glucocorticoid use (e.g., nutritional deficiency) as a contributing component to the osteoporosis burden in IBD [36]. van Staa et al also demonstrated an increase in fractures after adjusting for corticosteroid use [37].…”
Section: Nutritional Deficienciesmentioning
confidence: 94%